Surface modification of CuInS2 photocathodes with ruthenium co-catalysts for efficient solar water splitting - Chae, Sang Youn; Yoon, Noyoung; Park, Eun Duck; Joo, Oh Shim (Applied Surface Science, 2023)
In this work, the photoelectrochemical H2 production activity of CuInS2 photocathodes is investigated after sequential surface modification with a-MoSx, Pt, or Ru. Although Ru has much inferior electrocatalytic activity to Pt for hydrogen evolution reaction (HER), a Ru-modified CuInS2/a-MoSx photocathode shows higher photoelectrochemical (PEC) activities than a Pt-modified one. X-ray photoelectron spectroscopy (XPS), ultraviolet photoelectron spectroscopy (UPS), and other (photo)electrochemical characterizations were carried out for the surface-modified CuInS2 photocathode to reveal the origin of the high PEC activity. The energy level of Ru on CuInS2/a-MoSx photocathodes is more suitable for the electron transfer between semiconductor–metal-electrolytes, and it leads to a fast electron transient time during PEC reaction by the improved carrier lifetime. This result implies that the Ru modification of photocathodes can be one of potential strategies for tuning band alignment and improving PEC activities.
Keywords: Co catalysts; Electrocatalytic activity; Electrochemical characterizations; H 2 production; Hydrogen evolution reactions; Photoelectrochemicals; Production activity; Solar water splitting; Surface-modification; Surface-modified; Copper indium sulfide; HER; Molybdenum sulfide; Photoelectrochemical cell; Ruthenium